Hydrophilic glass surface processing treatment process

Through ultrasonic cleaning, chemical etching and physical vapor deposition technology, the composite hydrophilic coating of nanotitanium dioxide and tin oxide is formed, and combined with annealing treatment and self-healing anti-fouling coating, the problem of easy contamination on the surface of traditional glass is solved and the service life and optical properties of the glass are significantly improved.

CN119954402APending Publication Date: 2025-05-09SHAANXI TOPRAY SOLAR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510040618.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

Traditional glass surfaces are hydrophobic and are prone to adsorbing dust, dirt and moisture, resulting in a decrease in light transmittance and affecting the power generation efficiency of photovoltaic modules. In addition, existing hydrophilic glass technology has poor durability, poor optical performance, insufficient compatibility, and lack of self-cleaning and protection functions.

Method used

The glass surface is cleaned and etched by a combination of ultrasonic cleaning and chemical etching. Then, a composite hydrophilic coating of nanotitanium dioxide and tin oxide is deposited on the glass surface through physical vapor deposition technology, and annealed treatment is carried out to eliminate the stress in the coating, and finally a self-repair anti-fouling coating is applied to the glass surface.

Benefits of technology

It significantly improves the service life and optical properties of hydrophilic glass, reduces the amount of dust adhesion, improves light transmittance and power generation efficiency, and gives the glass good self-repair ability and anti-fouling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954402A_ABST
    Figure CN119954402A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophilic glass surface processing technology, and relates to the field of photovoltaic technology, and the hydrophilic glass surface processing technology comprises the following steps: firstly, finely cutting a glass substrate, controlling the cutting precision to be within + / -0.05 mm, then carrying out edge grinding treatment to make the edge roughness be less than 0.03 [mu] m, cleaning by adopting a mode of combining ultrasonic cleaning and chemical etching, and carrying out surface treatment on the glass substrate. The ultrasonic cleaning frequency is 40-60 kHz, the cleaning time is 15-25 minutes, the chemical etching solution is a hydrofluoric acid solution with the concentration of 3%-7%, and the etching time is 3-8 minutes; then, a hydrophilic coating is deposited on the surface of the glass by utilizing a physical vapor deposition (PVD) technology, impurities, defects and microscopic roughness on the surface of the glass can be effectively removed through an accurate glass substrate pretreatment step, a good foundation is provided for subsequent coating deposition, and the bonding strength of the coating and the surface of the glass is greatly improved; the adhesive force of the coating is improved by 40%-60% compared with that of a traditional process, and the service life of the hydrophilic glass is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaic technology, and more specifically, particularly relates to a hydrophilic glass surface processing technology. Background Art

[0002] In the energy field, with the growing demand for clean energy, the importance of photovoltaic power generation technology has become increasingly prominent. The performance of photovoltaic modules directly affects the power generation efficiency, and the surface performance of glass, as a key component of photovoltaic modules, has a crucial impact on the overall performance of the modules. Traditional glass surfaces usually have a certain degree of hydrophobicity, and are easy to absorb dust, dirt and moisture in outdoor environments, resulting in a decrease in light transmittance, which seriously affects the power generation efficiency of photovoltaic modules. According to statistics, in some areas with serious dust pollution, the power generation loss caused by glass surface pollution after 3-6 months of operation of photovoltaic modules can reach 15%-30%. In addition, frequent manual cleaning is not only costly, but may also cause damage to the modules. Although the existing hydrophilic glass technology has improved the surface performance of glass to a certain extent, there are still many shortcomings, such as poor hydrophilic persistence, unsatisfactory optical performance, compatibility with modules needs to be improved, and lack of effective self-cleaning and protection functions. Therefore, it is of great practical significance to develop an efficient and stable hydrophilic glass surface processing technology. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a hydrophilic glass surface processing technology to solve the above problems.

[0004] A hydrophilic glass surface processing process comprises the following steps: first, finely cutting a glass substrate, with the cutting accuracy controlled within ±0.05 mm, then grinding the edges to make the edge roughness less than 0.03 μm, then cleaning by combining ultrasonic cleaning and chemical etching, with the ultrasonic cleaning frequency of 40-60 kHz and the cleaning time of 15-25 minutes, and the chemical etching solution being a hydrofluoric acid solution with a concentration of 3%-7%, and the etching time of 3-8 minutes; then, using physical vapor deposition (PVD) technology to deposit a hydrophilic coating on the glass surface, with magnetron sputtering being used in the PVD process, and the target material It is a composite material of nano titanium dioxide (TiO2) and tin oxide (SnO2), in which nano titanium dioxide accounts for 60%-80%, the sputtering power is 150-300W, the argon gas flow rate is 40-80sccm, and the deposition time is 30-60 minutes to form a uniform hydrophilic coating with good adhesion; finally, the glass with the prepared hydrophilic coating is annealed, the annealing temperature is 300-500℃, the annealing time is 20-40 minutes, the heating rate is controlled at 5-10℃ / min, and the cooling rate is controlled at 3-6℃ / min, so as to eliminate the internal stress of the coating and improve the stability of the coating.

[0005] Preferably, during the pretreatment of the glass substrate, it is necessary to rinse with deionized water at least three times after chemical etching, and each rinse time is not less than 2 minutes to ensure that there is no chemical residue on the glass surface. During the physical vapor deposition (PVD) process, the vacuum degree in the reaction chamber is maintained at 5×10 -4 -2×10 -3 Pa, to ensure the stability of the sputtering process and the uniformity of the coating. Before depositing the hydrophilic coating, the glass surface is subjected to plasma activation treatment. The plasma treatment power is 100-200W, the treatment time is 5-10 minutes, and the treatment gas is a mixed gas of oxygen and nitrogen, wherein the volume ratio of oxygen to nitrogen is 1:2-1:3, to enhance the surface activity of the glass and the adhesion of the subsequent coating. During the plasma activation treatment, the surface temperature of the glass is maintained at 70-110°C to prevent the performance of the glass from being affected by excessively high or low temperature.

[0006] A hydrophilic glass, whose water contact angle is less than 30°, whose light transmittance in the wavelength range of 400-1100nm is greater than 92%, and after 1000 hours of outdoor exposure test, the water contact angle increases by no more than 8°, and the light transmittance decreases by no more than 4%. The hydrophilic glass surface has a micro-nano structure, the depth of the micro-nano structure is 0.1-0.3μm, and the spacing is 0.5-1μm. The micro-nano structure is prepared by a process combining photolithography and etching. The micro-nano structure can further improve the spreading performance of water on the glass surface and reduce the light reflection loss, so that the light reflectivity is reduced by 10%-15%.

[0007] Preferably, the hydrophilicity of the edge area of ​​the hydrophilic glass is slightly lower than that of the central area, and the water contact angle of the edge area is 10°-15° larger than that of the central area. The hydrophilicity gradient is achieved by adjusting the coating thickness or composition to prevent water accumulation at the edge from affecting the performance of the component. A self-repairing anti-fouling coating with a thickness of 15-30nm is coated on the surface of the hydrophilic glass. The coating is composed of a composite of an organic silicon polymer and nano zinc oxide. When the glass surface is slightly scratched or contaminated, the coating can automatically repair itself within a certain period of time to maintain the hydrophilicity and anti-fouling properties of the glass, so that the glass can recover to more than 90% of its initial performance within 48 hours after being slightly damaged. Rare earth element dopants are added to the hydrophilic glass during the preparation process, and the doping amount of rare earth elements is 0.05%-0.15%, which can improve the chemical stability and weather resistance of the glass and extend the service life of the glass in harsh environments by 20%-30%.

[0008] Compared with the prior art, the present invention has the following beneficial effects:

[0009] In the present invention, through precise glass substrate pretreatment steps, impurities, defects and micro-roughness on the glass surface can be effectively removed, providing a good foundation for subsequent coating deposition, greatly improving the bonding strength between the coating and the glass surface, and improving the adhesion of the coating by 40%-60% compared with traditional processes, significantly extending the service life of the hydrophilic glass.

[0010] In the present invention, by adopting a unique physical vapor deposition (PVD) technology, using a composite target of nano titanium dioxide and tin oxide, and accurately controlling sputtering parameters, a coating with high hydrophilicity and good optical properties can be formed on the glass surface. The coating can reduce the water contact angle of the glass to below 30°, effectively reducing the adhesion of dust and dirt. Under the same outdoor environment, the amount of dust adhesion is reduced by 70%-90% compared with ordinary glass. At the same time, the light transmittance within the wavelength range of 400-1100nm is greater than 92%, which significantly improves the power generation of photovoltaic modules. Experimental data show that the power generation can be increased by 20%-30%.

[0011] In the present invention, the activity and roughness of the glass surface are further enhanced through the plasma activation treatment step, which is beneficial to improving the adhesion and uniformity of the coating and improving the stability of the coating by 50%-70% in harsh environments.

[0012] In the present invention, a reasonably designed annealing process can effectively eliminate the internal stress of the coating, avoid cracking or peeling of the coating, and ensure the performance stability of the hydrophilic glass during long-term use. After long-term outdoor testing, the attenuation of its optical performance and hydrophilicity is much lower than that of products prepared by traditional processes.

[0013] In the present invention, the micro-nano structure design of the hydrophilic glass surface can effectively regulate the distribution and flow of the water film on the glass surface, reduce the reflection and refraction loss of light, reduce the light reflectivity by 10%-15%, and further improve the light transmittance of the glass and the power generation efficiency of the photovoltaic module.

[0014] In the present invention, the design of the hydrophilic gradient structure can optimize the moisture distribution according to the functional requirements of different areas of the glass, prevent the influence of water accumulation on the sealing performance of the component on the edge, improve the applicability and reliability of the hydrophilic glass in the photovoltaic component, and reduce the failure probability of the component due to moisture-related problems by 40%-60%.

[0015] In the present invention, the application of the self-repairing anti-fouling coating gives the glass good self-repairing ability and anti-fouling performance. When the glass surface is slightly scratched or contaminated, the coating can automatically repair itself within a certain period of time, maintaining the hydrophilicity and anti-fouling properties of the glass, reducing maintenance costs and frequency, and allowing the glass to recover to more than 90% of its initial performance within 48 hours after being slightly damaged.

[0016] In the present invention, the chemical stability and weather resistance of the glass are significantly improved by adding rare earth element dopants, the service life of the glass in harsh environments is extended by 20%-30%, and the replacement frequency and cost of photovoltaic modules are reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is the overall process flow topology diagram of the present invention;

[0018] Figure 2 is a topological diagram of the glass substrate pretreatment of the present invention;

[0019] Figure 3 It is a topological diagram of the preparation of the hydrophilic coating of the present invention;

[0020] Figure 4 It is the post-processing and inspection topology diagram of the present invention;

[0021] Figure 5 It is a topological diagram of the special structure and coating treatment of the present invention. DETAILED DESCRIPTION

[0022] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] See also Figure 1-Figure 5 The present invention provides a hydrophilic glass surface processing process, comprising the following steps: first, finely cutting the glass substrate, with the cutting accuracy controlled within ±0.05mm, then grinding the edge to make the edge roughness less than 0.03μm, then cleaning by combining ultrasonic cleaning and chemical etching, with the ultrasonic cleaning frequency of 40-60kHz, the cleaning time of 15-25 minutes, the chemical etching solution of 3%-7% hydrofluoric acid solution, and the etching time of 3-8 minutes; then, using physical vapor deposition (PVD) technology to deposit a hydrophilic coating on the glass surface, and using magnetron sputtering in the PVD process The target material is a composite material of nano-titanium dioxide (TiO2) and tin oxide (SnO2), in which nano-titanium dioxide accounts for 60%-80%, the sputtering power is 150-300W, the argon flow rate is 40-80sccm, and the deposition time is 30-60 minutes to form a uniform hydrophilic coating with good adhesion; finally, the glass with the prepared hydrophilic coating is annealed at a temperature of 300-500°C, an annealing time of 20-40 minutes, a heating rate of 5-10°C / min, and a cooling rate of 3-6°C / min, thereby eliminating the internal stress of the coating and improving the stability of the coating.

[0024] During the pretreatment of the glass substrate, it is necessary to rinse with deionized water at least three times after chemical etching, and each rinse time is not less than 2 minutes to ensure that there is no chemical residue on the glass surface. During the physical vapor deposition (PVD) process, the vacuum degree in the reaction chamber is maintained at 5×10 -4 -2×10 -3 Pa, to ensure the stability of the sputtering process and the uniformity of the coating. Before depositing the hydrophilic coating, the glass surface is subjected to plasma activation treatment. The plasma treatment power is 100-200W, the treatment time is 5-10 minutes, and the treatment gas is a mixture of oxygen and nitrogen. The volume ratio of oxygen to nitrogen is 1:2-1:3 to enhance the surface activity of the glass and the adhesion of the subsequent coating. During the plasma activation treatment, the glass surface temperature is maintained at 70-110°C to prevent the glass from affecting its performance due to excessively high or low temperature.

[0025] A hydrophilic glass has a water contact angle of less than 30° and a light transmittance of more than 92% within a wavelength range of 400-1100nm. After 1000 hours of outdoor exposure test, the water contact angle increases by no more than 8° and the light transmittance decreases by no more than 4%. The surface of the hydrophilic glass has a micro-nano structure with a depth of 0.1-0.3μm and a spacing of 0.5-1μm. The micro-nano structure is prepared by a process combining photolithography and etching. The micro-nano structure can further improve the spreading performance of water on the glass surface and reduce light reflection loss, thereby reducing the light reflectivity by 10%-15%.

[0026] The hydrophilicity of the edge area of ​​the hydrophilic glass is slightly lower than that of the central area, and the water contact angle of the edge area is 10°-15° larger than that of the central area. The hydrophilicity gradient is achieved by adjusting the coating thickness or composition to prevent water accumulation at the edge from affecting the performance of the component. A self-healing anti-fouling coating with a thickness of 15-30nm is coated on the surface of the hydrophilic glass. The coating is composed of a composite of silicone polymer and nano zinc oxide. When the glass surface is slightly scratched or contaminated, the coating can automatically repair itself within a certain period of time to maintain the hydrophilicity and anti-fouling properties of the glass, so that the glass can recover to more than 90% of its initial performance within 48 hours after slight damage. Rare earth element dopants are added to the hydrophilic glass during the preparation process. The doping amount of rare earth elements is 0.05%-0.15%, which can improve the chemical stability and weather resistance of the glass and extend the service life of the glass in harsh environments by 20%-30%.

[0027] Embodiment 1:

[0028] Process steps:

[0029] Pretreatment: Select ultra-white glass substrates with a size of 400mm×400mm and a thickness of 3mm, and use a high-precision laser cutting machine for cutting, with a cutting accuracy of ±0.03mm, and then use precision edge grinding equipment to grind the edges, and the edge roughness is controlled below 0.02μm. Then put the glass into an ultrasonic cleaning machine and ultrasonically clean it at a frequency of 50kHz for 20 minutes. The ultrasonic cleaning liquid is a mixture of deionized water and a small amount of special cleaning agent. Then soak it in a 5% hydrofluoric acid solution for chemical etching for 5 minutes, and finally rinse it with deionized water 3 times, each time for 2.5 minutes, to ensure that there are no impurities left on the glass surface.

[0030] Preparation of hydrophilic coating: The pretreated glass was placed in the PVD reaction chamber and magnetron sputtering was used. The target material was a composite material of nano-titanium dioxide and tin oxide with a nano-titanium dioxide ratio of 70%. The sputtering power was set to 200 W, the argon gas flow rate was 60 sccm, and the vacuum degree was 1×10 -3 The hydrophilic coating was uniformly deposited on the glass surface under the conditions of 4500 Pa and the coating thickness was about 0.2 μm.

[0031] Post-treatment and inspection: After deposition, the glass was transferred to an annealing furnace, heated to 400°C at a heating rate of 8°C / min, annealed for 30 minutes, and then cooled to room temperature at a cooling rate of 4°C / min. The prepared glass was quality tested, and the water contact angle was measured to be 28°, and the transmittance in the wavelength range of 400-1100nm was 93%.

[0032] Application effect: The hydrophilic glass was used for photovoltaic module encapsulation, and ethylene-vinyl acetate copolymer (EVA) was selected as the encapsulation material. The encapsulation was carried out for 15 minutes at 130°C and 0.9MPa. The photovoltaic module was installed in an outdoor area with a lot of dust and a certain humidity, and compared with ordinary glass photovoltaic modules. After 4 months of operation, the dust adhesion on the surface of the ordinary glass module reached 10g / m 2 , the light transmittance dropped to 75%, and the power generation decreased by 25%; while the dust adhesion on the surface of the hydrophilic glass component of this embodiment was only 2g / m 2 , the transmittance remains above 90%, and the power generation is only reduced by 6%, which has significant advantages over ordinary glass components.

[0033] Embodiment 2:

[0034] Process steps:

[0035] Pretreatment: Use a 3.5mm thick float glass substrate and cut it into 500mm×500mm specifications with a cutting accuracy of ±0.04mm and an edge roughness of 0.025μm after edge grinding. First, perform ultrasonic cleaning with an ultrasonic frequency of 45kHz for 22 minutes, then chemically etch with a 4% hydrofluoric acid solution for 4 minutes, and then rinse with deionized water 4 times, 3 minutes each time.

[0036] Preparation of hydrophilic coating: Plasma activation treatment was performed on the glass surface using a plasma generator with a power of 150W. The treatment gas was a mixture of oxygen and nitrogen in a volume ratio of 1:2.5. The treatment time was 8 minutes and the glass surface temperature was maintained at 90°C. Then PVD coating deposition was performed. The target material was a composite material of nano-titanium dioxide and tin oxide with a nano-titanium dioxide ratio of 75%. The sputtering power was 250W, the argon gas flow rate was 70sccm, and the vacuum was 8×10 -4 The hydrophilic coating with a thickness of about 0.23 μm was formed by deposition under the condition of 50 min.

[0037] Post-treatment and inspection: The glass was annealed at 450°C for 35 minutes, with a heating rate of 7°C / min and a cooling rate of 5°C / min. The test results showed that the water contact angle was 26° and the transmittance in the wavelength range of 400-1100nm was 94%.

[0038] Application effect: This hydrophilic glass was applied to photovoltaic modules, and the temperature during the packaging process was 135°C, the pressure was 1.1MPa, and the time was 17 minutes. After operating for 5 months in an outdoor environment with sufficient sunlight and slight wind and sand, the ordinary glass photovoltaic modules were eroded by dust, dirt and water, and obvious stains appeared on the surface, and the power generation efficiency was reduced by 20%; while the surface of the hydrophilic glass photovoltaic module of this embodiment was relatively clean, with only a small amount of dust accumulated on the edge, and the power generation efficiency was only reduced by 7%, which effectively ensured the stable power generation of the module.

[0039] Embodiment 3:

[0040] Process steps:

[0041] Pretreatment: Select a 4mm thick ultra-white glass substrate and cut it into a size of 450mm×450mm. The cutting accuracy is controlled at ±0.035mm and the edge grinding accuracy reaches 0.028μm. Ultrasonic cleaning frequency is 55kHz. After cleaning for 18 minutes, chemical etching is performed with 6% hydrofluoric acid solution for 6 minutes, and then fully rinsed with deionized water for 3 times, each time for 3.5 minutes.

[0042] Preparation of hydrophilic coating: plasma activation treatment was first performed, with a power of 180W, a treatment gas of oxygen and nitrogen mixed in a ratio of 1:2, a treatment time of 7 minutes, and a glass surface temperature maintained at 80°C. Then PVD deposition was performed, with a target material of a composite material of nano-titanium dioxide and tin oxide with a nano-titanium dioxide ratio of 65%, a sputtering power of 220W, an argon gas flow rate of 50sccm, and a vacuum of 1.5×10 -3 Pa for 40 minutes to obtain a hydrophilic coating with a thickness of about 0.21 μm. Then, a self-repairing antifouling coating composed of a composite of organic silicon polymer and nano zinc oxide was coated on the glass surface by spraying with a spraying pressure of 0.8 MPa and a coating thickness of about 25 nm.

[0043] Post-treatment and inspection: Annealing at 420°C for 30 minutes, heating rate 6°C / min, cooling rate 4°C / min. The water contact angle was 27° and the transmittance was 92.5%.

[0044] Application effect: The hydrophilic glass was used to encapsulate photovoltaic modules under the conditions of 140°C, 1.05MPa and 16 minutes. After operating for 6 months in an area with strong wind and industrial pollution, the surface of ordinary glass modules was scratched due to wind and sand wear, dust coverage and chemical corrosion, and the light transmittance was seriously reduced, and the power generation was reduced by 30%; while the surface of the hydrophilic glass module of this embodiment had only slight scratches, less dust adhesion, and the light transmittance was still maintained at more than 88%, and the power generation was reduced by 12%, showing good anti-wind and sand, anti-fouling and wear resistance, and effectively improving the power generation stability and durability of photovoltaic modules in harsh environments.

[0045] V. Comparison of Examples:

[0046] Hydrophilicity and dust adhesion: Example 2 has the smallest water contact angle of 26° and the strongest hydrophilicity. After running outdoors for the same time, the amount of dust adhesion on the surface is the least, indicating that its hydrophilicity performs best in practical applications; the water contact angle of Example 1 is 28°, and the amount of dust adhesion is second; although Example 3 has a water contact angle of 27°, due to the self-repairing anti-fouling coating on its surface, the amount of dust adhesion in windy and polluted environments is relatively small, but the overall hydrophilicity is slightly inferior to that of Example 2.

[0047] Light transmittance and stability: The light transmittance of Example 3 was 92.5% during the initial test, and it was still maintained above 88% after 6 months of outdoor operation, and the light transmittance stability was good; the initial light transmittance of Example 2 was 94%, and it still maintained a high level after 5 months; the light transmittance of Example 1 decreased relatively more after 4 months, indicating that the processes of Example 3 and Example 2 are superior to Example 1 in ensuring the stability of light transmittance.

[0048] Anti-fouling and wear-resistant performance: Since Example 3 is coated with a self-repairing anti-fouling coating on the surface, it exhibits good anti-fouling and wear-resistant performance in an environment with strong winds and industrial pollution. There are only slight scratches on the surface and little dust attachment. Example 1 and Example 2 perform well in an environment with ordinary dust and slight wind and sand, but their anti-fouling and wear-resistant performance in harsh environments is not as good as Example 3.

[0049] Comprehensive performance evaluation: In summary, Example 2 performs outstandingly in terms of hydrophilicity and dust adhesion, Example 3 has advantages in terms of anti-fouling, wear resistance and transmittance stability, and Example 1 has relatively balanced performance but is slightly inferior to the first two in some aspects. In practical applications, appropriate embodiment processes can be selected according to different usage environments and requirements. For example, in an environment with light dust pollution but high transmittance requirements, Example 2 can be preferred; in a severe windy and polluted environment, Example 3 is more suitable; and Example 1 can be applied to general outdoor environments, taking into account both cost and process operability while ensuring certain performance.

[0050] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A hydrophilic glass surface processing process, characterized in that: The method comprises the following steps: first, finely cutting the glass substrate, with the cutting accuracy controlled within ±0.05 mm, then grinding the edges to make the edge roughness less than 0.03 μm, and then cleaning the glass substrate by combining ultrasonic cleaning and chemical etching, with the ultrasonic cleaning frequency of 40-60 kHz and the cleaning time of 15-25 minutes. The chemical etching solution is a hydrofluoric acid solution with a concentration of 3%-7%, and the etching time is 3-8 minutes. Then, a hydrophilic coating is deposited on the glass surface by physical vapor deposition (PVD) technology, with magnetron sputtering being used in the PVD process, and the target material is nano-titanium dioxide ( The invention discloses a composite material of TiO2) and tin oxide (SnO2), wherein nano titanium dioxide accounts for 60%-80%, the sputtering power is 150-300W, the argon gas flow rate is 40-80sccm, and the deposition time is 30-60 minutes, so as to form a uniform hydrophilic coating with good adhesion; finally, the glass prepared with the hydrophilic coating is annealed, the annealing temperature is 300-500℃, the annealing time is 20-40 minutes, the heating rate is controlled at 5-10℃ / min, and the cooling rate is controlled at 3-6℃ / min, so as to eliminate the internal stress of the coating and improve the stability of the coating.

2. The hydrophilic glass surface processing process according to claim 1, characterized in that: During the pretreatment of the glass substrate, it needs to be rinsed with deionized water at least 3 times after chemical etching, with each rinse time not less than 2 minutes to ensure that there is no chemical residue on the glass surface.

3. The hydrophilic glass surface processing process according to claim 1, characterized in that: During the physical vapor deposition (PVD) process, the vacuum degree in the reaction chamber was maintained at 5×10 -4 -2×10 -3 Pa, to ensure the stability of the sputtering process and the uniformity of the coating.

4. The hydrophilic glass surface processing process according to claim 1, characterized in that: Before depositing the hydrophilic coating, the glass surface is subjected to plasma activation treatment, the plasma treatment power is 100-200W, the treatment time is 5-10 minutes, the treatment gas is a mixture of oxygen and nitrogen, wherein the volume ratio of oxygen to nitrogen is 1:2-1:3, so as to enhance the surface activity of the glass and the adhesion of the subsequent coating.

5. The hydrophilic glass surface processing process according to claim 4, characterized in that: During the plasma activation treatment, the surface temperature of the glass is maintained at 70-110° C. to prevent the performance of the glass from being affected by excessively high or low temperatures.

6. A hydrophilic glass, characterized in that: The invention is prepared by the process described in any one of claims 1 to 5, wherein the water contact angle is less than 30°, the light transmittance in the wavelength range of 400-1100 nm is greater than 92%, and after 1000 hours of outdoor exposure test, the water contact angle increases by no more than 8°, and the light transmittance decreases by no more than 4%.

7. The hydrophilic glass according to claim 6, characterized in that: The hydrophilic glass surface has a micro-nano structure with a depth of 0.1-0.3 μm and a spacing of 0.5-1 μm. It is prepared by a process combining photolithography and etching. The micro-nano structure can further improve the spreading performance of water on the glass surface and reduce light reflection loss, reducing the light reflectivity by 10%-15%.

8. The hydrophilic glass according to claim 6, characterized in that: The hydrophilicity of the edge area of ​​the hydrophilic glass is slightly lower than that of the central area, and the water contact angle of the edge area is 10°-15° larger than that of the central area. The hydrophilicity gradient is achieved by adjusting the coating thickness or composition to prevent water accumulation at the edge from affecting component performance.

9. The hydrophilic glass according to claim 6, characterized in that: A self-healing anti-fouling coating with a thickness of 15-30nm is coated on the surface of the hydrophilic glass. The coating is a composite of silicone polymer and nano zinc oxide. When the glass surface is slightly scratched or contaminated, the coating can automatically repair itself within a certain period of time, maintaining the hydrophilicity and anti-fouling properties of the glass, allowing the glass to recover to more than 90% of its original performance within 48 hours after slight damage.

10. The hydrophilic glass according to claim 6, characterized in that: The hydrophilic glass is doped with rare earth element dopants during the preparation process. The doping amount of the rare earth element is 0.05%-0.15%, which can improve the chemical stability and weather resistance of the glass and extend the service life of the glass in harsh environments by 20%-30%.